Methylenetetrahydrofolate reductase polymorphic variants C677T and A1298C in rectal cancer in Slavic population: significance for cancer risk and response to chemoradiotherapy - Stanojevic, Aleksandra; Spasic, Jelena; Marinkovic, Mladen; Stojanovic-Rundic, Suzana; Jankovic, Radmila; Djuric, Ana; Zoidakis, Jerome; Fijneman, Remond J. A.; Castellvi-Bel, Sergi; Cavic, Milena (Frontiers in Genetics, 2024)
Background: Methylenetetrahydrofolate reductase (MTHFR) single nucleotide polymorphisms (SNPs) have been suggested as risk, prognostic, and predictive factors for colorectal cancer in various populations, but have not been validated so far. The aim of this study was to examine the association of MTHFR C677T (rs1801133) and A1298C (rs1801131) single nucleotide polymorphisms with the risk of rectal cancer as well as the response to neoadjuvant chemoradiotherapy (nCRT) based on 5-Fluorouracil (5-FU)/leucovorin (LV) in the locally advanced setting. Patients and methods: This casecontrol study included 119 healthy controls and 97 patients with locally advanced rectal cancer (LARC). For MTHFR genotyping, restriction fragment length polymorphism analysis (PCR-RFLP) was employed. Results: In silico analysis highlighted that SNPs C677T and A1298T correlate with MTHFR gene expression, and that gene expression profile correlates with cancer risk and stage. Using dominant and recessive models, it was found that the MTHFR 677CC vs 677CT+677TT have increased risk of cancer development (odds ratio (OR): 2.27; 95% confidence interval (CI): 1.30-3.95, p= 0.002) as well as 677CC+677CT compared to 677TT (OR: 4.18, 95% CI: 1.16-14.99, p=0.014). MTHFR 1298AA also shown increased risk for cancer development compared to 1298AC+1298CC (OR:2.0, 95% CI:1.20-3.59, p=0.035) Statistical analysis of combined genotypes highlighted the protective role of CT/AC combined genotype (OR: 3.15 95% CI: 1.576-6.279, p=0.002) while the CC/AA genotype showed an increased risk for rectal cancer development (OR: 2.499, 95% CI: 1.246-5.081, p=0.016) The carriers of the 677C/1298A haplotype had the highest risk for developing rectal cancer (OR: 1.74; 95% CI: 1.198-2.530, p=0.002) while the 677T/1298C haplotype seems to provide a protective effect. (OR: 0.44; 95%CI 0.248-0.795, p=0.003).No significant association with response to chemoradiotherapy was found. Conclusion: Our data point to MTHFR 667C allele and 1298A alleles as low-penetrance risk factors for rectal cancer in our population. To the best of our knowledge, this is the first study of this type performed on the Slavic population in the Western Balkan, as various population-based factors might also be significant our findings can be used for future meta-analyses and the construction of genetic cancer risk prediction panels